Smart university image: Branding strategy in private universities - Luckyardi, Senny; Hurriyati , Ratih; Disman, Disman; Dewi Dirgantari, Puspo (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
ABSTRACT This study aims to develop a new construct, Smart University Image (SUI), as a branding strategy in private universities. It is necessary due to the limitations of brand image theory in the context of a Smart University (SU), which is considered inconsistent and insufficient semantically or functionally. The research was analyzed by using Structural Equation Modeling (SEM). The respondents were 215 students from private universities, including in the SU category in West Java Province, one of the provinces with the highest number of private universities in Indonesia. The results showed that Technology Readiness (TR), E-Service Quality (ESQ), and E-Information Quality (EIQ) were significantly influenced by Value Co-Creation (VCC) and SUI at private universities in West Java. VCC is able to mediate the relationship between ESQ, EIQ, and SUI. It is concluded that SUI is an important value of branding strategy through VCC between students and the university.